Posterity or Prosperity? Critiquing and Refiguring Prosperity Theologies in an Ecological Age - Swoboda, A.J. (2015)
At the beginning of the twenty-first century, prosperity theologies have simultaneously received a warm reception by some and a critical cold shoulder by others. With emotive responses provoked on both sides, what cannot be ignored is the influence prosperity thinking has, and will have, on the global church. Yet, little to no attention has been devoted to the intersection between prosperity theology and the issues surrounding the ecological crisis, such as climate change, environmental degradation, human greed, and wanton consumerism. Does such an intersection exist? This article explores this question by contrasting prosperity theology’s divine economy and agrarianism’s great economy. In sum, it suggests that the uncritical reception of prosperity teachings—though they speak pointedly to real, felt human needs—can ultimately create ecologically harmful, if not anti-ecological, modes of thinking and living within its adherents.
Keywords: Ecotheology -- prosperity theology -- environment -- Pentecostalism -- ecology